Antimicrobial performance on molds isolated from muffin and antioxidant capacity of raw and roasted coffee oils (Coffea arabica L.) (Research, Society and Development, 2020)
Molds are the main agents that cause the deterioration of the cake, making it inappropriate for human consumption and reducing its commercial and nutritional value. Biopreservation techniques can improve the quality and safety of bakery products by inhibiting the fungi growth. Raw and roasted coffee oils have bioactive, antioxidant and antimicrobial properties, being an alternative to a partial or a total replacement of artificial preservatives. This study aimed to isolate the microorganisms of the muffin cake and evaluate the antifungal properties of these oils against isolated molds and determine the total phenolic compounds and evaluate the antioxidant capacity of the oils by the DPPH and FRAP methods. After isolating the cake”s fungi culture, macroscopic and microscopic evaluations were performed. The molds were characterized as filamentous and belonging to the genus Trichothecium sp., Aspergillus sp. and Penicillium sp. However, the oils did not show antifungal activity relative to the fungi isolated from the cake. Roasted coffee oil had a higher content of total phenolic compounds in relation to crude coffee oil (946.84 and 155.76 mg of gallic acid/100g of extract, respectively). For the antioxidant capacity by the DPPH method there was no difference between the oils and they were lower than in the FRAP method, which was more efficient. The oils tested do not have a potential antifungal effect, but roasted coffee oil has a higher antioxidant capacity than crude coffee oil by the FRAP method, corroborating the total phenolic concentration identified.